Proceedings of the 2007 International ACM Conference on Conference on Supporting Group Work - GROUP '07 2007
DOI: 10.1145/1316624.1316663
|View full text |Cite
|
Sign up to set email alerts
|

Creating, destroying, and restoring value in wikipedia

Abstract: Wikipedia's brilliance and curse is that any user can edit any of the encyclopedia entries. We introduce the notion of the impact of an edit, measured by the number of times the edited version is viewed. Using several datasets, including recent logs of all article views, we show that an overwhelming majority of the viewed words were written by frequent editors and that this majority is increasing. Similarly, using the same impact measure, we show that the probability of a typical article view being damaged is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
192
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(199 citation statements)
references
References 16 publications
2
192
0
3
Order By: Relevance
“…When epochs=600, RMSE for training data and checking data are shown in (5). Figure 12, shows the output of the system.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When epochs=600, RMSE for training data and checking data are shown in (5). Figure 12, shows the output of the system.…”
Section: Methodsmentioning
confidence: 99%
“…Lih [19] measured the quality of Wikipedia articles by the independent variables of linking, number of edits, number of authors, article size, and other metadata from Wikipedia. Priedhorsky et al [5] have examined the impact of editing and editors on the Wikipedia value. Stein and Hess [20] have demonstrated that there is a significant relationship between the featured articles and increasing number of authors.…”
Section: Determining the Quality Of Wikipedia Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common application is detection and measurement of popular news topics or events [13][14][15][16][17]. The data have also been used to study the dynamics of Wikipedia itself [18][19][20]. Social applications include evaluating toponym importance in order to make type size decisions for maps [21], measuring the flow of concepts across the world [22], and estimating the popularity of politicians and political parties [23].…”
Section: Author Summarymentioning
confidence: 99%
“…Fortunately, those who damage articles seem poorly motivated. Priedhorsky et al [56] observes that 71% of damaging edits exhibit 'nonsense' or 'offensive' attributes. However, [35] indicates that Wikipedia's growing popularity will invite motivated malicious users, such as spammers, who have financial incentive to evade protections.…”
Section: Cautions For Value Usagementioning
confidence: 99%